Kumak's fish : a tall tale from the far north - Bania, Michael, 1944- (Alaska Northwest Books, 2004)
On a beautiful Arctic morning when Kumak and his family go ice fishing, Kumak hooks what seems like an enormous fish, and the entire village gets involved.